(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Dapsone derivatives Viz., 4, 4â€™-sulfonylbis(N-((1H-pyrrol-2-yl)methylene)aniline) (SBPMA) and 2-dimethylamino-5-[(4-4-[(4-dimethylamino-benzylidene)-amino]-benzenesulfonyl-phenylimino)-methyl]-benzene (DBBPB), a new class of corrosion inhibitors have been synthesized and their corrosion inhibition efficiency on mild steel in 0.5 M H2SO4 was investigated by mass loss,Â Tafel polarization and AC impedance measurements. Potentiodynamic polarization studies showed that, these compounds behave as mixed type of corrosion inhibitors. The adsorption process was found to obey Langmuir isotherm model. Electrochemical impedance spectroscopy (EIS) studies revealed that polarization resistance (RP) increases and double layer capacitance (Cdl) decreases as the concentration of the inhibitors increases. Various thermodynamic parameters for the adsorption of inhibitors on mild steel were computed and discussed. FTIR, EDX and SEM analyses were performed to study the film persistency of the inhibitors.